2013
DOI: 10.4102/sajpsychiatry.v19i2.415
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and HIV sexual risk behaviour among University of Limpopo students

Abstract: <div class="column"><p><strong>Background. </strong><span>Little attention has been paid to the role of poor mental health among young people with regard to HIV risk behaviour and HIV prevention in Africa.<br /> </span></p><p><strong>Objective. </strong><span>To determine the association between mental health, substance use and HIV sexual risk behaviour among a sample of university students in South Africa. </span></p><p>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…In this study the theme Alcohol and illicit drug use highlighted the perceived relationship between HIV, alcohol and drugs use and included the sub-theme Alcohol use as a community norm. Substance use, including alcohol and illicit drug use, was perceived to be a major risk behaviour that adolescents engage in and this finding is supported by the results of studies reported in the litera ture (Parry et al, 2004;Pengpid et a l, 2013). Respondents illustrated this by making the following statements: "They smoke Dagga."…”
Section: Alcohol and Illicit Drug Usesupporting
confidence: 64%
See 1 more Smart Citation
“…In this study the theme Alcohol and illicit drug use highlighted the perceived relationship between HIV, alcohol and drugs use and included the sub-theme Alcohol use as a community norm. Substance use, including alcohol and illicit drug use, was perceived to be a major risk behaviour that adolescents engage in and this finding is supported by the results of studies reported in the litera ture (Parry et al, 2004;Pengpid et a l, 2013). Respondents illustrated this by making the following statements: "They smoke Dagga."…”
Section: Alcohol and Illicit Drug Usesupporting
confidence: 64%
“…In South Africa, a study conducted by Nduna, Jewkes, Dunkle, Shai, and Colman (2010) found that there was an association between mental health problems, especially depression, and risky sexual behaviour such as transactional sex among females, as well as an association between transactional sex, perpetrating intimate partner violence and rape, and non-condom use among males. More recently, mental illness and mental health symptoms have been associated with risk for HIV infection in South Africa (Pengpid, Peltzer & Skaal, 2013). Youth with psychiatric disorders lack adequate sexual communication skills which are essential for safer sexual behaviour, are susceptible to negative peer norms with regards to risk taking, report low self-efficacy for condom use, and display decreased assertiveness and ability to negotiate safer sex (Flisher & Gevers, 2010).…”
Section: Risk Behaviour Associated With Hiv Infectionmentioning
confidence: 98%
“…This finding contrasts with the majority of studies from North America that find depressive symptoms to be predictive of greater likelihood of reporting HIV risk behaviors (48,49). Among men in South Africa, the relationship between depressive symptoms and HIV risk behavior has been mixed (33,50,51). For example in a study among young men aged 15 to 26 years in the Eastern Cape region of South Africa, young men with depressive symptoms were more likely to report ever engaging in transactional sex (51).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with poor mental health conditions such as depressive symptoms may have decreased ability to discern HIV sexual risk behaviors and to take steps to avoid them. Multiple studies in South Africa, have documented associations between depressive symptoms and HIV risk behaviors (33,34). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, a large number of students live away from university premises and are, therefore, relatively not bound by the students' residential code of conduct. Such a context coupled with the young people's psychological, social and economic challenges as well as their tendency to test boundaries, may lead students to experiment with casual sexual relationships, drugs, and other risky lifestyles (Pengpid et al, 2013). The above characteristics have led some scholars to use the metaphor of the university's social context as a fertile breeding ground for the HIV virus (Asante and Oti-Boadi, 2013;Mwamwenda, 2014).…”
Section: Introductionmentioning
confidence: 99%